Hepatocellular Carcinoma Cells with Downregulated ZEB2 Become Resistant to Resveratrol by Concomitant Induction of ABCG2 Expression [2] - Balçık-Erçin, Pelin; Çetin, Metin; Yalim-Camci, Irem; Uygur, T.; Yağci, Tamer (NLM (Medline), 2020)
In hepatocellular carcinoma (HCC), the presence of cancer stem cells (CSCs) have been linked to drug resistance, epithelial-mesenchymal transition (EMT), and cancer relapse. This study investigates the expression profile of ZEB1, ZEB2, ABCG2 in HCC-CSCs, and the role of EMT promoter ZEB2 in cells treated with resveratrol. The expression of ZEB1, ZEB2 and ABCG2 transcripts were analyzed in CD133^(+)/CD44^(+) cells isolated from the PLC/PRF/5 cell line. ZEB2-dependent ABCG2 gene expression and the effects of resveratrol on proliferation, cell cycle and apoptosis were explored in SNU398 cell clones. An inverse correlation between ZEB1/ZEB2 and ABCG2 levels were observed both in CSCs and in ZEB2-knock-down cells. The resveratrol treatment significantly decreased cell viability, while promoting cell cycle arrest in ZEB2-independent manner. Interestingly, resveratrol-treated cells with low levels of ZEB2 were resistant to apoptosis. The interplay of expression levels of ABCG2 and ZEB family EMT transcription factors may play a role in establishing CSC-like phenotype in HCC cells resistant to resveratrol. This record is sourced from MEDLINE/PubMed, a database of the U.S. National Library of Medicine
Keywords: ABCG2; cancer stem cells; drug resistance; epithelial-to-mesenchymal transition; hepatocellular carcinoma; resveratrol; ZEB2